''Let them move the mail with transistors instead of brains'': Labour convergence in posts and telecommunications, 1972––3. (1st October 2010) - ,; ,
Abstract : The United States employs more postal workers than any other country, including China. The American Postal Workers Union and the National Association of Letter Carriers represent the majority of these workers. Since the APWU's formation in 1970, both unions have declined to merge with one another or any other union; however, in the early 1970s, the APWU and the NALC participated in merger talks with the Communications Workers of America. This article explores the proposed merger between the APWU, the NALC, and the CWA to try to clarify why these unions continually declined to effect ''labour convergence''.